Effect of Se treatment on the volatile compounds in broccoli. (1st February 2017) - Lv, Jiayu; Wu, Jie; Zuo, Jinhua; Fan, Linlin; Shi, Junyan; Gao, Lipu; Li, Miao; Wang, Qing
Highlights: Treatment increased the sensory and flavour quality of broccoli. Se treatment decreased the content of alcohols and sulfide compounds in broccoli. The content of Se was improved, while the content of S was reduced after Se treatment. Se treatment inhibited the respiration rate and ethylene production of broccoli during the storage. Abstract: Broccoli contains high levels of bioactive compounds but deteriorates and senesces easily. In the present study, freshly harvested broccoli was treated with selenite and stored at two different temperatures. The effect of selenite treatment on sensory quality and postharvest physiology were analyzed. Volatile components were assessed by HS-SPME combined with GC–MS and EN. The metabolism of Se and S was also examined. Results indicated that Se treatment had a significant effect on maintaining the sensory quality, suppressing the respiration intensity and ethylene production, as well as increasing the content of Se and decreasing the content of S. In particular, significant differences in the composition of volatile compounds were present between control and Se-treated. The differences were mainly due to differences in alcohols and sulfide compounds. These results demonstrate that Se treatment can have a positive effect on maintaining quality and enhancing its sensory quality through the release of volatile compounds.